2023
DOI: 10.1371/journal.pone.0288631
|View full text |Cite
|
Sign up to set email alerts
|

Artificial intelligence for detecting temporomandibular joint osteoarthritis using radiographic image data: A systematic review and meta-analysis of diagnostic test accuracy

Abstract: In this review, we assessed the diagnostic efficiency of artificial intelligence (AI) models in detecting temporomandibular joint osteoarthritis (TMJOA) using radiographic imaging data. Based upon the PRISMA guidelines, a systematic review of studies published between January 2010 and January 2023 was conducted using PubMed, Web of Science, Scopus, and Embase. Articles on the accuracy of AI to detect TMJOA or degenerative changes by radiographic imaging were selected. The characteristics and diagnostic informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 55 publications
0
1
0
Order By: Relevance
“…The 2023 study by Almasan [123] showed that the pooled sensitivity and specificity of AI in panoramic radiograph TMJOA detection accounted for 0.76 (95% CI 0.35-0.95) and 0.79 (95% CI 0.75-0.83), respectively. Similar results related to this topic were reported by Xu [126], who reported a pooled sensitivity, specificity, and area under the curve (AUC) of 80%, 90%, and 92%, respectively. A more comprehensive study carried out by Jha et al [125] analyzed 17 articles for the automated diagnosis of masticatory muscle disorders, TMJ osteoarthrosis, internal derangement, and disc perforation.…”
Section: Tmj Evaluationsupporting
confidence: 86%
See 1 more Smart Citation
“…The 2023 study by Almasan [123] showed that the pooled sensitivity and specificity of AI in panoramic radiograph TMJOA detection accounted for 0.76 (95% CI 0.35-0.95) and 0.79 (95% CI 0.75-0.83), respectively. Similar results related to this topic were reported by Xu [126], who reported a pooled sensitivity, specificity, and area under the curve (AUC) of 80%, 90%, and 92%, respectively. A more comprehensive study carried out by Jha et al [125] analyzed 17 articles for the automated diagnosis of masticatory muscle disorders, TMJ osteoarthrosis, internal derangement, and disc perforation.…”
Section: Tmj Evaluationsupporting
confidence: 86%
“…The few reviews and meta-analyses conducted on this topic showed the overall moderate-to-good accuracy of the tested models in TMJOA detection [122][123][124][125][126]. The 2023 study by Almasan [123] showed that the pooled sensitivity and specificity of AI in panoramic radiograph TMJOA detection accounted for 0.76 (95% CI 0.35-0.95) and 0.79 (95% CI 0.75-0.83), respectively.…”
Section: Tmj Evaluationmentioning
confidence: 99%
“…Using panoramic radiography images, the sensitivity and speci city of the deep learning model for diagnosing TMJ osteoarthritis were equivalent to those of experts 30 . When using CBCT images, the area under the curve (AUC) for diagnostic accuracy of TMJ osteoarthritis was 0.86 31 . A ne-tuned model for articular disc displacement using MRI showed excellent predictive performance (AUC = 0.8775) 32 .…”
Section: Introductionmentioning
confidence: 99%